The Structure of Authority and its Epistemological Basics in Farabi’s Political Philosophy - Ali, Hala; Alkhatib, Ali (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research deals with structure of power and its concept in Farabi’s political philosophy, by analyzing his basic thesis of Utopia, and analyzing the relation between governor and the parish, and explaining the political connections that control this city, like the stratification and ideological structure down to the relationship between the prophecy and philosophy, all this through systematic reading deals with the power of speech and its relationships, and the semantic context through which these ideas emerged, and the nature of cultural relationships that control thought and cultural production in that era. By understanding Farabi’s political ideas and their situation of speech context emerged the category of (good authority) as a reflection of the structure of that era, and an alternative to the category of existing power at that time which was based on tradition and the sanctity of hereditary rule. Here Farabi’s summon the pronouncements of the Greek speech and reconstructing and integrating them in the context of the Islamic intellectual on the one hand becomes a necessity which is required to the building of the political alternative of religious feudal authority, and on the other hand its unique feature and characteristic distinguish the Farabian philosophy through his building a philosophical pattern which combines rationality and inspiration.